1989
DOI: 10.4141/cjas89-018
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Maternal and Fetal Tissue Zinc, Iron, Manganese and Selenium Concentrations in Bovine

Abstract: GoonnnerNn, S. R. aNp CrnrsrBNsrN D. A. 1989

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
9
1

Year Published

1992
1992
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 5 publications
3
9
1
Order By: Relevance
“…Maternal liver Cu was negatively correlated with fetal age, this results agree with the results obtained by (Gonneratne and Christensen, 1989b). While (Graham et al, 1994) found that maternal liver Cu was not correlated with fetal size.…”
Section: Discussionsupporting
confidence: 89%
“…Maternal liver Cu was negatively correlated with fetal age, this results agree with the results obtained by (Gonneratne and Christensen, 1989b). While (Graham et al, 1994) found that maternal liver Cu was not correlated with fetal size.…”
Section: Discussionsupporting
confidence: 89%
“…Ovine maternal and fetal liver Cu were negatively correlated in this and previous reports(Gonneratne and Christensen, 1989b). Presence of significant negative relationship between age of the fetus and maternal liver Cu concentration as well as the relationships between maternal liver and amniotic and allantoic fluid Cu concentrations were significantly negative, while the relationship between age of the fetus and maternal plasma, fetal liver, amniotic fluid, allantoic fluid and fetal kidney Cu concentrations were significantly positive might indicate that, the dam and fetus depended on the maternal liver Cu contents during gestation (Abd Elghany et al, 2011) and liver Cu can be used as an indicator of the Cu status(Johnston et al, 2014) through gestation and fetuses had a capacity to sequester maternal Cu, even when the dam was Cu deficient(Graham et al, 1994) Parkinson (1981).…”
supporting
confidence: 81%
“…Simultaneously, the Se concentration in the serum of calves born to cows fed with Se-enriched yeast was 1.3-fold higher in comparison with that found in calves born to cows that received inorganic salts. The efficiency of Se transfer across the placenta found in this research is lower than that estimated previously in cattle as a correlation of Se concentrations between fetus-dam in liver (r = 0.65; Gooneratne and Christensen 1989) and in whole doi: 10.17221/86/2016-CJAS blood (r = 0.63; Patterson et al 2013). It may be assumed that the main reason for the higher value of this relationship presented in the cited studies was the comparison of Se concentration in the liver and in the whole blood.…”
Section: Diet-cow Se Transfer Efficiencycontrasting
confidence: 51%